Pranata Jinayah: Kasus Persekusi terhadap Perempuan di Pasir Putih Kambang - Sri Insani, Silvi; Rido Saprinaldo Putra; Putri, Helvia; Elvionita, Elsa; Ayu Putri, Weldra (Forschungsforum Law Journal, 2025)
The case of persecution of two women in Pasir Putih Kambang, Pesisir Selatan Regency, West Sumatra, reflects a series of incidents that show weaknesses in law enforcement regarding sexual violence and gender discrimination. This incident involved physical and psychological attacks on two cafe patrons by around 300 people for no apparent reason, resulting in trauma and damage to the victims. The authorities' handling of this case highlights the challenges in protecting victims and delivering justice. This research uses a qualitative approach to gain an in-depth understanding of the chronology of the incident, the perception of the relevant community, and the psychological impact of the victims. The case study method was used to analyze this case as a representation of broader problems in the implementation of laws related to sexual violence. The research location in Pasir Putih Kambang was chosen because the incident was interesting for further research, especially related to law enforcement and protection of victims. The research subjects are local communities and related parties who can provide insight into this problem. The aim of this research is to understand the phenomenon of persecution and sexual violence in the context of this case, as well as identifying factors that influence law enforcement and protection of victims. It is hoped that this research can provide more effective policy recommendations in preventing and handling similar cases in the future, in order to create a safer and fairer environment for all individuals.